Pandemic as an Organizational Paradigm for Neonatal Care: Long-Term Impact of Mother–Infant Separation Practice During COVID-19 - Maria Di Chiara; Benedetta De Santis; Flavia Gloria; Fabio Natale; Annarita Ferazzoli; Gianluigi Laccetta; Alessandra Marciano; Roberto Brunelli; Gianluca Terrin (Children)
Objectives: The hospital organizational model can have an impact on people’s health. A critical lesson can be drawn from the pandemic. The possible negative sequelae of the practice of separation of maternal–infant dyads adopted during an infant’s first SARS-CoV-2 pandemic infection on infants have not been considered. Our purpose was to investigate the short- and long-term effects on neonates born to SARS-CoV-2 infected mothers of two different mother–infant dyad management strategies after birth (Separation vs. Rooming-In). Methods: This prospective cohort study enrolled 60 pregnant women who tested positive for SARS-CoV-2 infection and their newborns. We identified two cohorts of study based on mother–infant dyad management after delivery: Cohort A (Separation) and Cohort B (Rooming-In). Inclusion criteria were neonates born from mothers infected with SARS-CoV-2 during the pregnancy undergoing or not undergoing separation. Main Outcome: Rate of exclusive breastfeeding at 6 months of age was the primary outcome. The rate of mother–infant transmission of SARS-CoV-2 infection, growth, incidence of acute infections and neurodevelopment up to 12 months of life were also evaluated. Results: In total, 60 mother–infant dyads (maternal age 30.6 vs. 33.8 years, p = 0.335; gestational age 39.0 vs. 38.9 weeks, p = 0.451) were enrolled at delivery, and 53 dyads completed the study at the 6-month follow-up. Baseline clinical characteristics were similar between the two cohorts. At 6-month follow-up, the rate of breastfeeding was significantly decreased in Cohort A compared with Cohort B (4% vs. 46%, p < 0.001). The rate of SARS-CoV-2 infection was similar between the two cohorts of the study. Weight gain at 6 months of life was significantly higher in Cohort A compared to Cohort B (8129 g, 95% CI, 7562 to 8695; vs. 7393 g, 95% CI, 6912 to 7874; p = 0.005). No differences were detected in terms of rate of acute neonatal infections and neurodevelopment outcomes. Conclusions: The separation practice led to a reduction in the rate of breastfeeding after discharge and to a consequently increased implementation of formula milk, which might justify the alarming increased weight gain of newborns who did not undergo the Rooming-In practice. Given the potential of recurrent outbreaks of other viral pandemics, our results suggest more caution early in life towards the disruption of consolidated procedures that may have long-term consequences. However, the COVID-19 pandemic offered a unique context to observe the effects of temporary mother–infant separation; clinicians should be reassured that the temporary separation practice did not affect neurodevelopment and be aware that it could be considered an option, at least if Rooming-In cannot be carried out due to severe reasons such as lack of staff or adequate space.